2021
DOI: 10.1038/s41598-021-01119-3
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal prediction of the COVID-19 pandemic in US counties: modeling with a deep LSTM neural network

Abstract: Prediction of complex epidemiological systems such as COVID-19 is challenging on many grounds. Commonly used compartmental models struggle to handle an epidemiological process that evolves rapidly and is spatially heterogeneous. On the other hand, machine learning methods are limited at the beginning of the pandemics due to small data size for training. We propose a deep learning approach to predict future COVID-19 infection cases and deaths 1 to 4 weeks ahead at the fine granularity of US counties. The multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 55 publications
0
28
0
Order By: Relevance
“…Coronavirus disease 2019 (COVID-19) is a public health crisis that has afflicted more than 225 countries all over the world [ 1 , 2 ]. This highly communicable disease is expected to have lingering effects on public health, human mobility, and the environment, disrupting social relations and economic wellbeing, and transforming the social and spatial structure of the city [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Studies have shown that a reduction in mandatory and discretionary mobility can essentially curtail the severity of the pandemic and associated health risks [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID-19) is a public health crisis that has afflicted more than 225 countries all over the world [ 1 , 2 ]. This highly communicable disease is expected to have lingering effects on public health, human mobility, and the environment, disrupting social relations and economic wellbeing, and transforming the social and spatial structure of the city [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Studies have shown that a reduction in mandatory and discretionary mobility can essentially curtail the severity of the pandemic and associated health risks [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the great success in solving sequence data, LSTM has been applied to COVID-19 detection tasks and achieved great performances [ 71 , 72 , 73 , 74 , 75 ]. For instance, ArunKumar et al [ 76 ] proposed a deep learning approach that modified the traditional LSTM with a new activation function for predicting the infected cases and death cases of the COVID-19 dataset.…”
Section: Approachmentioning
confidence: 99%
“…Numerous predictions use algorithmic machine learning models, such as the long short-term memory recurrent neural network model; an example is Nikparvar et al [15], which predicts county-level incidence. A similar model predicts hospitalization and death at a national level after vaccination [16].…”
Section: Introductionmentioning
confidence: 99%